PENGARUH KOMITMEN, KOMPETENSI, DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZHENSHIP BEHAVIOUR (OCB) PEGAWAI PUSKESMAS BROMO MEDAN - Endang Kurnia Ningsih (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
OCB is often interpreted as behavior that exceeds formal obligations (extra roles) that are not related to direct compensation. However, some permanent employees of the Medan Puskesmas Bromo seemed to be united with their work, even though they were in accordance with their educational background. Some important factors that can increase OCB include commitment, competence, and organizational culture. This study aims to analyze the influence of commitment, competence, and organizational culture on organizational citizenship behavior. This type of research is quantitative descriptive and the nature of this research is explanatory research. The population in this study were permanent employees of Puskesmas Bromo totaling 35people and the sample of this study was a saturated sample (census). Analysis of the data used is multiple linear regression. The results showed first that commitment has a positive and significant effect on organizational citizenship behavior, secondly that competence has a positive and significant effect on organizational citizenship behavior, thirdly that organizational culture has a positive and significant effect on organizational citizenship behavior, fourthly that commitment, competence and Organizational culture has a significant effect on the organizational citizenship behavior of the  Employee Medan Puskesman Bromo